Self‐Expansion Based Multi‐Patterning for 2D Materials Fabrication beyond the Lithographical Limit - Borhade, Poonam Subhash; Chen, Tawat; Chen, Ding‐Rui; Chen, Yu‐Xiang; Yao, Yu‐Chi; Yen, Zhi‐Long; Tsai, Chun Hsiung; Hsieh, Ya‐Ping; Hofmann, Mario (Small (Weinheim an der Bergstrasse, Germany), 2024)
Two‐dimensional (2D) materials are promising successors for silicon transistor channels in ultimately scaled devices, necessitating significant research efforts to study their behavior at nanoscopic length scales. Unfortunately, current research has limited itself to direct patterning approaches, which limit the achievable resolution to the diffraction limit and introduce unwanted defects into the 2D material. The potential of multi‐patterning to fabricate 2D materials features with unprecedented precision and low complexity at large scale is demonstrated here. By combining lithographic patterning of a mandrel and bottom‐up self‐expansion, this approach enables pattern resolution one order of magnitude below the lithographical resolution. In‐depth characterization of the self‐expansion double patterning (SEDP) process reveals the ability to manipulate the critical dimension with nanometer precision through a self‐limiting and temperature‐controlled oxidation process. These results indicate that the SEDP process can regain the quality and morphology of the 2D material, as shown by high‐resolution microscopy and optical spectroscopy. This approach is shown to open up new avenues for research into high‐performance, ultra‐scaled 2D materials devices for future electronics. A versatile multi‐patterning approach is introduced as a tool to support researchers in studying 2D materials integration into nanoscaled electronic devices. The critical dimension of the self‐aligned process does not depend on the diffraction limit but on a bottom‐up expansion step. This method supports scalable 2D materials‐based electronics at high quality for future studies in the field.